The use of a nerve stimulation test to confirm sacrococcygeal epidural needle placement in cats. (January 2015) - Otero, Pablo E; Verdier, Natali; Zaccagnini, Andrea S; Fuensalida, Santiago E; Tarragona, Lisa; Portela, Diego A
Abstract: Objective: To determine if a nerve stimulation test (NST) could act as a monitoring technique to confirm sacrococcygeal epidural needle placement in cats. Study design: Prospective experimental trial in a clinical setting. Animals: Twenty-four adult cats, scheduled for a therapeutic procedure where epidural anesthesia was indicated. Methods: Under general anesthesia, an insulated needle was inserted through the S3 -Cd1 intervertebral space guided by the application of a fixed electrical current (0.7 mA) until a motor response was obtained. The NST was considered positive when the epidural nerve stimulation produced a motor response of the muscles of the tail, whereas it was considered negative when no motor response was evoked. In the NST positive cases, 0.3 mL kg −1 of 0.5% bupivacaine was administrated before needle withdrawal. Ten minutes after injection, epidural blockade was confirmed by the loss of perineal (anal), and pelvic limbs reflexes (patellar and withdrawal). Results: The use of a fixed electrical stimulation current of 0.7 mA resulted in correct prediction of sacrococcygeal epidural injection, corroborated by post bupivacaine loss of perineal and pelvic limb reflexes, in 95.8% of the cases. Conclusion and clinical relevance: This study demonstrates the feasibility of using, in a clinical setting, an electrical stimulation test as an objective and in real-time method to confirm sacrococcygeal epidural needle placement in cats.